“Hero of Our Time” as Archetype of Plot and Images in “Enchanted Wanderer” - V. G. Mekhtiev (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The results of a comparative analysis of the novel “The Enchanted Wanderer” by N. S. Leskov and the novel “Hero of Our Time” by M. Yu. Lermontov are presented. Particular attention is paid to the image ofthe prince, parodic in relation to Pechorin and “superfluous people”, as well as the storyline of Ivan Flyagin, echoing the line of Maxim Maksimych. The novelty of the study is due to both the little study of the connections between Leskov the artist and the work of Lermontov, and the insufficient coverage of the issue of the historical existence of Lermontov’s novel. It is shown that stylistic tendencies that are stable for Russian literature of the 19th century differ among writers. Along with this, the question is raised about Leskov’s critical view of the Pechorin type; in his story in the foreground is the hero named Ap. Grigoriev “meek” as opposed to the demonic, “predatory” type. It is noted that in the plot of the novel “A Hero of Our Time” Maxim Makimych, personifying a folk character, takes a subordinate place, this is explained by Lermontov’s sympathy for a demonic personality. The author points out that in “The Enchanted Wanderer”, on the contrary, there is a change in the function of the hero; the prince turns into a marginal character, and the Russian righteous man takes the place of the plot center.